2018
DOI: 10.21037/tp.2017.08.02
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic management of attention deficit hyperactivity disorder in children and adolescents: a review for practitioners

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common neurobehavioral disorder in children and adolescents. ADHD affects multiple aspects of an individual's life and functioning in family, social, and academic realms. Effective management of ADHD is necessary for children and adolescents and may include non-pharmacologic treatments, pharmacologic therapy including use of stimulant and non-stimulant medications, or a combination of the different treatment modalities. In general, medications used to treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 30 publications
0
70
0
1
Order By: Relevance
“…In addition, the ClinicalTrials.gov database was searched using the following keywords: (ADHD and methylphenidate). This search strategy was augmented through a hand search of reference lists for eligible articles as well as relevant clinical guidelines and review articles 2,7,10,21 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the ClinicalTrials.gov database was searched using the following keywords: (ADHD and methylphenidate). This search strategy was augmented through a hand search of reference lists for eligible articles as well as relevant clinical guidelines and review articles 2,7,10,21 .…”
Section: Methodsmentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) can present with symptoms encompassing inattentive, hyperactivity and impulsivity domains, and is associated with significant psychosocial and academic dysfunctions 1 . ADHD is the most common neurobehavioral disorder amongst children and adolescents 2 . In addition, children with probable ADHD have been reported to have a 16-point decrease in IQ compared to those without ADHD 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that not only genetic factors but also environmental factors (e.g., infections, early traumas, and drugs), age, sociodemographic factors (e.g., ethnicity and socioeconomic status), and a complex interplay between these factors have a role in the pathophysiology of different psychiatric diseases, such as anxiety disorder (1, 11), bipolar disorder (5), schizophrenia (6, 12), major depressive disorder (2, 13, 14), autism spectrum disorder (15), and ADHD (16). Close association between different psychiatric disorders, such as anxiety disorder and major depressive disorder, has been demonstrated (5, 1721).…”
Section: Introductionmentioning
confidence: 99%
“…1 Since the symptoms affect social and academic achievement and physical condition, treatment is often required; pharmacological agents, both stimulants and nonstimulants, are frequently used in its treatment. 2 Atomoxetine is a selective, presynaptic, norepinephrine reuptake inhibitor also known as a NET inhibitor. It was the first non-stimulant medication to receive FDA approval for the treatment of ADHD.…”
Section: Introductionmentioning
confidence: 99%